2006
DOI: 10.1111/j.1365-2559.2006.02513.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of immunohistochemistry—issues concerning methods, utility and semiquantitative assessment II

Abstract: Immunohistochemistry is entering its fourth decade of use on formalin-fixed paraffin-embedded tissues. Over this period the method has evolved to become a major part of the practice of diagnostic surgical pathology worldwide. From the beginning immunohistochemistry has been adapted to provide a range of markers of cell lineage and tissue type, with particular application to the diagnosis and classification of tumours. In this modality immunohistochemical methods were employed simply as 'special stains', the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
374
0
8

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 479 publications
(384 citation statements)
references
References 48 publications
2
374
0
8
Order By: Relevance
“…There is debate among pathologists as to where the absolute ''sweet spot'' is for optimal section thickness. Taylor and Levenson (2006) reported that this ''sweet spot'' was approximately 5 mm and that ''that uniform preparation of FFPE sections that are less than 5 mm in thickness is not possible.'' In contrast, the recommended thickness for performing the Hercept test is 4 mm; and for many pharmas (including ours), the standard thickness of a histologic section is 3 mm (Wolff et al 2007) (Figure 4).…”
Section: Section Thicknessmentioning
confidence: 99%
“…There is debate among pathologists as to where the absolute ''sweet spot'' is for optimal section thickness. Taylor and Levenson (2006) reported that this ''sweet spot'' was approximately 5 mm and that ''that uniform preparation of FFPE sections that are less than 5 mm in thickness is not possible.'' In contrast, the recommended thickness for performing the Hercept test is 4 mm; and for many pharmas (including ours), the standard thickness of a histologic section is 3 mm (Wolff et al 2007) (Figure 4).…”
Section: Section Thicknessmentioning
confidence: 99%
“…Briefly, one of the five sets of tissue was used, consisting of 40 µm sections taken every 200 µm starting rostral to the LC and continuing past the caudal edge of the LC. Immunohistochemical staining was carried out in 2 batches using identical methods, timing, reagents, buffers, and antibodies over a 2-week period to minimize any potential differences (Taylor and Levenson, 2006). Each batch contained tissues from half of the rats in each treatment group, and they were coded to blind the investigators.…”
Section: Mild Stress and Fos Expression In Lc Neuronsmentioning
confidence: 99%
“…It has been shown that ERCC1 immunodetection faces several methodological challenges including tissue processing, rates of interobserver agreement, geographic variation in protein expression and, most importantly, lack of the standardized cutoff value in semi-quantitative IHC [39][40][41]. It has been also reported that the most frequently used antibody 8F1 has not been specific for ERCC1 [42].…”
Section: Discussionmentioning
confidence: 99%